PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP HARGA SAHAM INDUSTRI MAKANAN DAN MINUMAN DI BEI - RIANISARI, ALFRIDA (Fakultas Ekonomi Universitas Tadulako, 2018)
This study aims to determine the effect of simultaneous liquidity, leverage and profitability to stock prices and the partial influence of liquidity, leverage and profitability to stock prices in food and beverage industry listed on Indonesia Stock Exchange (IDX). This study uses the entire food and beverage industry population listed in Indonesia Stock Exchange (IDX) in 2012 until 2016 as many as 16 companies. Sampling is done by purposive sampling. The sample used in this study as many as 11 companies listed on the Indonesia Stock Exchange (IDX). Data analysis method used is panel data regression analysis using EViews 9 program. The results stated that during the period 2012-2016 (1) simultaneously liquidity, leverage and profitability have an effect on signifikan to stock price in food and beverage industry which listed in Indonesia Stock Exchange (IDX), (2) liquidity has a positive and significant effect on stock price, (3) leverage have positive and insignificant effect to stock price, (4) profitability has a positive and significant effect on stock prices in food and beverage industry listed in Indonesia Stock Exchange (IDX).